TOXICITY TEST OF Eusideroxylon zwageri BARK EXTRACT ON LIVER HISTOPATHOLOGY PARENCHYMATOUS DEGENERATION AND FATTY DEGENERATION - A'idah, Nurul; Aspriyanto, Didit; Krishnawan Firdaus, I Wayan Arya; Sukmana, Bayu Indra; Wydiamala, Erida (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Ironwood bark extract can be developed into an alternative herbal medicine for wound healing because it contains phenolics, flavonoids, and proanthocyanidins which can act as an antioxidant. Before being used as an herbal medicine, it is necessary to ensure its safety through an toxicity test. Purpose: To find out whether there is no toxic effect on the orally administration of ironwood bark extract (Eusideroxylon zwageri) at the doses of 1,250 mg/kgBW, 2,750 mg/kgBW, and 4,750 mg/kgBW to the livers of Wistar rats (Rattus norvegicus) based on histopathological appearance of parenchymatous degeneration and fatty degeneration. Methods: This research is purely experimental with a posttest only with control design. The sample in this study were 16 Wistar rats which were divided into  4 groups, namely the control group which was only  administered distilled water and the treatment groups P1, P2, P3 which were administered ironwood bark extrac at the doses of 1,250 mg/kg BW, 2,750 mg/kg BW, and 4,750 mg/kgBW of 2x1 ml every 24 hours for 14 days. Results: The average percentages of histopathological appearance of parenchymatous degeneration and fatty degeneration in the K, P1, P2, and P3 groups showed a score of 0 which was categorized as normal. Data analysis showed that there were no significant differences between groups P1, P2, and P3 with the control group. Conclusion: Ironwood bark extract doses of 1,250 mg/kg BW, 2,750 mg/kg BW, and 4,750 mg/kg BW had no toxic effect on the liver of Wistar rats based on histopathological appearance of parenchymatous degeneration and fatty degeneration.